The Stacks project

Lemma 30.20.3. Let $A$ be a Noetherian ring. Let $I \subset A$ be an ideal. Let $f : X \to \mathop{\mathrm{Spec}}(A)$ be a proper morphism. Let $\mathcal{F}$ be a coherent sheaf on $X$. Then for every $p \geq 0$ there exists an integer $c \geq 0$ such that

  1. the multiplication map $I^{n - c} \otimes H^ p(X, I^ c\mathcal{F}) \to H^ p(X, I^ n\mathcal{F})$ is surjective for all $n \geq c$,

  2. the image of $H^ p(X, I^{n + m}\mathcal{F}) \to H^ p(X, I^ n\mathcal{F})$ is contained in the submodule $I^{m - e} H^ p(X, I^ n\mathcal{F})$ where $e = \max (0, c - n)$ for $n + m \geq c$, $n, m \geq 0$,

  3. we have

    \[ \mathop{\mathrm{Ker}}(H^ p(X, I^ n\mathcal{F}) \to H^ p(X, \mathcal{F})) = \mathop{\mathrm{Ker}}(H^ p(X, I^ n\mathcal{F}) \to H^ p(X, I^{n - c}\mathcal{F})) \]

    for $n \geq c$,

  4. there are maps $I^ nH^ p(X, \mathcal{F}) \to H^ p(X, I^{n - c}\mathcal{F})$ for $n \geq c$ such that the compositions

    \[ H^ p(X, I^ n\mathcal{F}) \to I^{n - c}H^ p(X, \mathcal{F}) \to H^ p(X, I^{n - 2c}\mathcal{F}) \]

    and

    \[ I^ nH^ p(X, \mathcal{F}) \to H^ p(X, I^{n - c}\mathcal{F}) \to I^{n - 2c}H^ p(X, \mathcal{F}) \]

    for $n \geq 2c$ are the canonical ones, and

  5. the inverse systems $(H^ p(X, I^ n\mathcal{F}))$ and $(I^ nH^ p(X, \mathcal{F}))$ are pro-isomorphic.

Proof. Write $M_ n = H^ p(X, I^ n\mathcal{F})$ for $n \geq 1$ and $M_0 = H^ p(X, \mathcal{F})$ so that we have maps $\ldots \to M_3 \to M_2 \to M_1 \to M_0$. Setting $B = \bigoplus _{n \geq 0} I^ n$, then $M = \bigoplus _{n \geq 0} M_ n$ is a finite graded $B$-module, see Lemma 30.20.1. Observe that the products $B_ n \otimes M_ m \to M_{m + n}$, $a \otimes m \mapsto a \cdot m$ are compatible with the maps in our inverse system in the sense that the diagrams

\[ \xymatrix{ B_ n \otimes _ A M_ m \ar[r] \ar[d] & M_{n + m} \ar[d] \\ B_ n \otimes _ A M_{m'} \ar[r] & M_{n + m'} } \]

commute for $n, m' \geq 0$ and $m \geq m'$.

Proof of (1). Choose $d_1, \ldots , d_ t \geq 0$ and $x_ i \in M_{d_ i}$ such that $M$ is generated by $x_1, \ldots , x_ t$ over $B$. For any $c \geq \max \{ d_ i\} $ we conclude that $B_{n - c} \cdot M_ c = M_ n$ for $n \geq c$ and we conclude (1) is true.

Proof of (2). Let $c$ be as in the proof of (1). Let $n + m \geq c$. We have $M_{n + m} = B_{n + m - c} \cdot M_ c$. If $c > n$ then we use $M_ c \to M_ n$ and the compatibility of products with transition maps pointed out above to conclude that the image of $M_{n + m} \to M_ n$ is contained in $I^{n + m - c}M_ n$. If $c \leq n$, then we write $M_{n + m} = B_ m \cdot B_{n - c} \cdot M_ c = B_ m \cdot M_ n$ to see that the image is contained in $I^ m M_ n$. This proves (2).

Let $K_ n \subset M_ n$ be the kernel of the map $M_ n \to M_0$. The compatibility of products with transition maps pointed out above shows that $K = \bigoplus K_ n \subset M$ is a graded $B$-submodule. As $B$ is Noetherian and $M$ is a finitely generated graded $B$-module, this shows that $K$ is a finitely generated graded $B$-module. Choose $d'_1, \ldots , d'_{t'} \geq 0$ and $y_ i \in K_{d'_ i}$ such that $K$ is generated by $y_1, \ldots , y_{t'}$ over $B$. Set $c = \max (d'_ i, d'_ j)$. Since $y_ i \in \mathop{\mathrm{Ker}}(M_{d'_ i} \to M_0)$ we see that $B_ n \cdot y_ i \subset \mathop{\mathrm{Ker}}(M_{n + d'_ i} \to M_ n)$. In this way we see that $K_ n = \mathop{\mathrm{Ker}}(M_ n \to M_{n - c})$ for $n \geq c$. This proves (3).

Consider the following commutative solid diagram

\[ \xymatrix{ I^ n \otimes _ A M_0 \ar[r] \ar[d] & I^ nM_0 \ar[r] \ar@{..>}[d] & M_0 \ar[d] \\ M_ n \ar[r] & M_{n - c} \ar[r] & M_0 } \]

Since the kernel of the surjective arrow $I^ n \otimes _ A M_0 \to I^ nM_0$ maps into $K_ n$ by the above we obtain the dotted arrow and the composition $I^ nM_0 \to M_{n - c} \to M_0$ is the canonical map. Then clearly the composition $I^ nM_0 \to M_{n - c} \to I^{n - 2c}M_0$ is the canonical map for $n \geq 2c$. Consider the composition $M_ n \to I^{n - c}M_0 \to M_{n - 2c}$. The first map sends an element of the form $a \cdot m$ with $a \in I^{n - c}$ and $m \in M_ c$ to $a m'$ where $m'$ is the image of $m$ in $M_0$. Then the second map sends this to $a \cdot m'$ in $M_{n - 2c}$ and we see (4) is true.

Part (5) is an immediate consequence of (4) and the definition of morphisms of pro-objects. $\square$


Comments (1)

Comment #7348 by Yijin Wang on

Maybe there is a typo in the proof of lemma 30.20.3: In paragraph four,the last but two lines,I think 'we see that B_n⋅y_i⊂Ker(M_{n+d_i}→M_n)' should be 'we see that B_n⋅y_i⊂Ker(M_{n+d'_i}→M_n)' .


Post a comment

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.




In order to prevent bots from posting comments, we would like you to prove that you are human. You can do this by filling in the name of the current tag in the following input field. As a reminder, this is tag 02OA. Beware of the difference between the letter 'O' and the digit '0'.